Training in Smart Financial Management for Cilengkrang Village's MSMEs - Angela, Aurora; Hidayat, Vinny Stephanie; Oktavianti, Oktavianti; Dewi, Nunik Lestari; Monalisa, Yani (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2025)
The goal of this community service project in Cilengkrang Village is to improve financial literacy and MSME (Micro, Small, and Medium Enterprises) actors' comprehension of effective financial planning. The program focuses on using financial planning techniques that are relevant to local MSMEs' real-world situations in order to promote business growth and maintain their financial stability. This event took place in Cilengkrang Village on October 28 and November 4, 2025, and 26 persons took part. Among the strategies used to encourage participants' active participation were conversations and interactive counseling.   The results of the activity show that Cilengkrang Village MSME actors now comprehend the need of sound financial planning and the processes involved.